Courbes de croissance fœtale non ajustées et personnalisées: une étude comparative dans une population du Sud du Sahara - Diakhaté, Abdoulaye; Ndiaye, Mame Diarra; Guèye, Mamour (Pan Africa Medical Journal, 2021)
The purpose of this study was to compare the unadjusted EPOPé M0 curve with the customized Gardosi curve in the diagnosis of small-for gestational-age (SGA) fetuses in a sub-Saharan population. We compared the Gardosi et al. and EPOPé M0 classifications. Classification differences were analyzed according to patient characteristics and obstetric conditions. Data collected from FileMaker software were analyzed using SPSS 20.0 and R Studio software. The statistical tests were carried out according to applicability conditions. Alpha risk was set at 0.05. The Gardosi curve showed that the rate of SGA newborns was higher (31.4% versus 28.9%) and did not differ between overweight and normal-weight women. The rate of severe SGA in preterm infants was also higher (23.6 versus 19.7%). Diseases were more frequent in newborns classified as severe SGA by the customized growth curve. The customized curve is recommended for the sub-Saharan Africa population
Keywords: Age gestationnel; Gardosi; EPOPé M0; courbes de croissance; Magatte Mbaye; Pape Moctar Faye; Université Cheikh Anta Diop; Moussa Diallo